THE EFFECT OF TRAINING & DEVELOPMENT AND MOTIVATION ON JOB SATISFACTION IN MICRO AND SMALL-SIZED ENTERPRISES’ MANAGERS IN PLAJU ULU VILLAGE - Yanur Ariska; Zunaidah Zunaidah; Afriyadi Cahyadi (JEMBATAN, 2015)
Micro and small enterprises have a great contribution to the country’s economy. However the lack of managers’ skills and abilities cause obstacles that affect the level of job satisfaction. In order to maximize the job satisfaction, MSEs’ managers need training and development and motivation. Training & development aims to increase managers’ skills and abilities. Motivation will give positive impact and increase satisfaction if a manager is able to expand his/her business. This study aims to know whether there is effect between Training & development and motivation on job satisfaction. This study is conducted on MSEs’ managers in Plaju Ulu Village. The number of samples is 78 managers as respondents, and the sampling technique is stratified random sampling. The analysis method used in this study is multiple regression analysis. The test result shows that Training & development and motivation have a significant and positive effect on job satisfaction. But Training & development do not has a partial effect on job satisfaction, while motivation has a significant and positive effect on job satisfaction. Coefficient determination shows that 24,6% variance of job satisfaction can be explained by independent variables in this study, while the rest 74,6% can be explained by others variable such as as innovation, committment, leadership, and personality that are not discussed in this study.Keywords : Development, Job Satisfaction, Micro and Small Enterprises Motivation, Training